If Transit is Free will Older Adults use it More? A Longitudinal Analysis - Meredith Alousi-Jones; Ahmed El-Geneidy (Findings)
Free public transit for older adults is a policy often advocated for to increase ridership and reduce their dependence on automobiles. In July 2023 public transit became free on the island of Montréal for older adults (65+). Drawing from longitudinal repeated survey data collected in February 2023 and September 2023 and in-depth interviews collected in November 2023, we study the impacts of free public transit fare policy on older adults’ (65+) frequency of public transit use and satisfaction with service. We did not observe any change in public transit use among those who anticipated increased use in the before period, nor among those who anticipated no change in their use after the implementation of the free fare policy. We observed a positive change in the perception of the convenience of public transit after the implementation of the free fare policy for older adults.